Immunohistochemical analysis of glucocorticoid receptor expression in early breast cancer and its influence on response to treatment with neoadjuvant systemic therapy - Sraka, Marjetka; Gazić, Babara; Drev, Primož; Grašič Kuhar, Cvetka (Onkologija : Slovenian Journal of Oncology, 2024)
Background: The glucocorticoid receptor (GR) is differentially expressed on tumour and immune cells in breast cancer, and its expression may depend on the molecular subtype of the cancer, and it may also influence the response to neoadjuvant systemic therapy. Our primary aim is to introduce reliable immunohistochemical staining with anti-GR antibodies, and our second aim is to evaluate the expression of GR in breast cancer samples and to study whether it is expressed differently in different subtypes and whether its expression has an impact on the response to neoadjuvant systemic therapy. Methods: In the preclinical part of the research, we selected a reliable antibody against GR, and then we calibrated and validated the immunohistochemical staining procedure with the selected antibody. In the clinical part of the research, we evaluated the expression of GR on tumour and immune cells in breast cancer. Samples from 162 patients were selected prospectively as part of the AKRA study, which took place at the Institute of Oncology Ljubljana, and later analysed. We also obtained data on the associated tumour. Results: We introduced reliable immunohistochemical staining with antibodies against GR and evaluated its expression on tumour and immune cells. On tumour cells, GR was positive in the triple- -negative subtype in 93.5%, in the HER2-positive subtype in 88.4% and in the luminal B subtype in 87.5%; the difference between the subtypes was not statistically significant (p = 0.746). A complete pathological response to neoadjuvant systemic therapy was present in the case of positive GR in 31.8%, and in the case of negative GR in 22.2%, which was also not statistically significantly different (p = 0.589). Expression on immune cells was present in all samples on ≥ 80% cells with an intensity level of 3, so we did not analyse these results. Conclusions: We successfully introduced immunohistochemical staining for glucocorticoid receptor and evaluated its expression on the samples, but we failed to demonstrate the association of GR expression with subtypes and response to neoadjuvant systemic therapy.